2015
DOI: 10.4172/2161-0401.s5-003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Sieves as a New, Highly Efficient, Inexpensive and Reusable Catalyst for N-Ter-Butoxycarbonylation of Amines

Abstract: General Procedure for BOC Protection of Amines: Di-tertbutyl dicarbonate (1 mmol) and Molecular sieves 4A° (0.1 mmol) were added to a solution of amine (1 mmol), and the reaction mixture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Durvasula and Khanna disclosed the MS 4A catalysed chemoselective N-tert-butoxycarbonylation of amines at room temperature, under solvent-free conditions. 35 The method was successfully applied for acyclic, aromatic and sterically hindered amines and provided the appropriate protected amines with moderate to excellent yields (28-98%). MS 4A provides a green alternative as a catalyst instead of the bases and Lewis acids that were previously used in the Boc-protection of amines.…”
Section: Acylationmentioning
confidence: 99%
“…Durvasula and Khanna disclosed the MS 4A catalysed chemoselective N-tert-butoxycarbonylation of amines at room temperature, under solvent-free conditions. 35 The method was successfully applied for acyclic, aromatic and sterically hindered amines and provided the appropriate protected amines with moderate to excellent yields (28-98%). MS 4A provides a green alternative as a catalyst instead of the bases and Lewis acids that were previously used in the Boc-protection of amines.…”
Section: Acylationmentioning
confidence: 99%
“…The most conventional method for tert -butoxycarbonylation uses di- tert -butyl dicarbonate (Boc 2 O, I , Scheme a) . However, this method usually requires a long reaction time and high-temperature conditions due to the mild electrophilicity of the I . , On the other hand, the use of highly electrophilic tert -butyl chloroformate (BocCl, IV ) will enable rapid tert -butoxycarbonylation; however, IV is not commercially available because it is unstable and rapidly decomposes at temperatures over 10 °C (Scheme b) . Multiple studies have reported the preparation of IV from phosgene ( III ) and tert -butyl alkoxide or t -BuOH and the use of IV for the following tert -butoxycarbonylation. , However, the use of highly toxic and volatile III , which requires special care in handling, decreases the utility of these methods.…”
Section: Introductionmentioning
confidence: 99%
“…Other catalysts that can be used in the N-Boc protection of amines prepared in the presence of Lewis acid such ZnCl4, 20 LiClO4, 21 HClO4, 22 Cu (BF4)2, 23 Zn (ClO4).6H2O, 24 La (NO3)3, 25 FeCl3, 26 Bi (NO3)3.5H2O, 27 InCl3, InBr3, 28 CsF, 29 I2, 30 Me2SBr2, 31 (CF3)2CHOH, 32 etc. Also used Brønsted acids including that Thiourea, 33 Thioglycouril, 34 Guanidine HCl, 35 Sulphamic acid, 36 Saccharin Sulfonic acid, 37 Succinamide Sulphamic acid, 38 and molecular sieves 39 etc. Nowadays, an acid-functionalized catalysts such as silica-supported sulfonic acid, Titania supported Nanoporous sulfonic acid, Nanoporous Na + Montmorillonite supported sulfonic acid, amberlyst-15, H3PW12O40 mesoporous silica acid, and Montmorillonite K10 or KSF, etc.…”
Section: Introductionmentioning
confidence: 99%